Molecular imaging in the management of cervical cancer - Chyong-Huey Lai (Journal of the Formosan Medical Association, 2012)
Positron emission tomography (PET), magnetic resonance imaging (MRI), and integrated 18-fluorodeoxyglucose (18F-FDG) PET/computed tomography are valuable techniques for assessing prognosis, treatment response after the completion of concurrent chemoradiation, suspicious or documented recurrence, unexplained post therapy elevations in tumor markers, and the response to salvage treatment when managing cervical cancer. However, PET plays a limited role in the primary staging of MRI-defined node-negative patients. Currently, 18F-FDG is still the only tracer approved for routine use, but several novel targeting PET compounds, high-Tesla MRI machines, diffusion-weighted imaging without contrast, and dynamic nuclear polarized-enhanced 13C-MR spectroscopic imaging may hold promising applications.